Pengaruh Penambahan Bubur Rumput Laut (Eucheuma Cottoni)Terhadap Sifatorganoleptik Dan Kadar Iodium Dodol Rumput Laut - Dian Safitri; Igde Widiada; Iketut Swiryajaya; Reni Sofiyatin (Jurnal Gizi Prima (Prime Nutrition Journal), 2018)
Background. Iodine Deficiency Disorder (IDD) is still a nutritional problem in Indonesia, Riskesdas (2007) reached 62.3% of IDD problem. Seaweed especially rich in essential nutrients iodine. In an effort to diversify the use of seaweed can be made into a semi-moist food is seaweed dodol. Dodol semi-moist food is greenish white and supple. Research Methods. The study design using completely randomized design (CRD) with one factor, namely the addition of seaweed porridge with 3-level experiments. To analyze the characteristic organoleptic properties were analyzed using Analysis Of Variance (One Way ANOVA) at the 95% confidence level (α0.05) followed by Tukey test. Research Result. The addition of seaweed porridge did not significantly affect the color, flavor, and texture seaweed dodol (p>0.05), but significantly affected the smell of seaweed dodol (p<0.05). Dodol with t3 treatment has a smell that is most preferred by 3.76 scale (rather like approaching the like), and for the parameters of color, flavor and texture in the treatment of t3 in the category rather like approaching like. The addition of seaweed porridge has a significant effect on the iodine content seaweed dodol (p<0.05). Conclusion. The addition of seaweed porridge did not significantly affect the color, flavor, and texture seaweed  dodol  (p>0.05),  but  significantly affected  the  smell  and  iodine  content  of  seaweed  dodol (p<0.05).